A study of compressive strength and air purifying capacity of a photocatalytic rice hull ash geopolymer concrete as alternative to conventional concrete - Batayola, Annie Rose R.; Juanga, Jean Marie V. (2020)
In recent years, Using Rise hull ash as alternative to conventional concrete mix become more significant in today?s architectural and engineering building structure. Most of this by-product material is currently dumped in landfills, creating a threat to the environment. Geopolymer concrete is a ?new? material that does not need the presence of Portland cement as a binder. Instead, the source of materials such as rice hull ash, that are rich in Silicon (Si) and Aluminium (Al), are activated by alkaline liquids to produce the binder. This thesis reports the details of development of the process of making rice hull ash-based geopolymer concrete. Addition to the agro-waste product use is a material that have the ability to purify air. Pollution controlling and smog-eating properties induced in a cementitious material were identified recently. It was discovered that this material had the ability to reduce certain pollutants from surrounding air, and this reduction in the concentration of the pollutants depends upon the surrounding conditions and the amount of exposed area. These properties induced in cementitious material were mainly due to the photocatalytic action of TiO2, which under the influence of sunlight acts as a catalyst and triggers chemical reaction due to that decomposition of dirt particles take place on the concrete?s surface, also it reacts with certain pollutants that contribute to smog, breaking it under the presence of sunlight and accelerating their natural oxidation process. This material has already found relevant applications, and is being used in a variety of projects such as self-cleaning walls and in the reduction of urban pollutants and serves multiple purpose. Furthermore, the main focus of this study is to incorporate the two products as one building material.
Thesis (BS Architecture)--University of the Philippines Mindanao, 2020